Implikasi Karakter Ruang Bermain Terhadap Biofilia Anak Usia Sekolah di Pulau Belakang Padang - Carissa Dinar Aguspriyanti; Alda Aulia Safitri; M. Hafish Pradesta Varro; Zahwa Rheina Habibah; Gladies Imanda Utami Rangkuty (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
To address sustainability challenges caused by climate change, it is essential to foster environmental awareness among children in coastal areas from an early age. The aim of this study was to examine the implications of play space characteristics on school-age children's affinity for nature, or biophilia, through a case study of Belakang Padang Island in the hinterland area of Batam City, Riau Islands, Indonesia. A descriptive qualitative approach was employed, utilising data collection methods such as mental mapping, participatory observation, and interviews. The findings indicated that the play spaces on the island exhibit both spatial and non-spatial characteristics and can be categorised into three main zones: land, transition, and sea. Children’s love for nature is reflected in their preference for play locations, sensory enjoyment of natural elements, a desire to explore nature, and curiosity about the natural world. Strategic and accessible play spaces allow for active interaction with natural elements, while types of play and social interactions strengthen children’s emotional attachment to the environment.